Diagnóstico y tratamiento en otorrinolaringología Cirugía de cabeza y cuello - Lalwani, Anil K. (McGraw-Hill's AccessMedicina., 2020)
Head and neck surgery in otorhinolaryngology is a unique subspecialty in Medicine that addresses the medical and surgical treatment of conditions that affect the ears, nose, throat and neck; the attention that the physician must give to the senses includes smell, taste, as well as balance and hearing. As a specialty, it interacts with other medical and surgical subspecialties, including allergology and immunology, endocrinology, gastroenterology, hematology, neurology, neurosurgery, oncology, ophthalmology, pediatrics, plastic and reconstructive surgery, pulmonology, radiological oncology, rehabilitation medicine , rheumatology, thoracic surgery, to name a few. In addition, this specialty provides care for young and mature people, men and women, as well as benign and malignant diseases.